Manatees - Grack, Rachel, (Rachel A. Koestler-Grack), 1973-; Downs, Kieran (Minneapolis, Minnesota : Bellwether Media, 2024)
"Relevant images match informative text in this introduction to why manatees are at risk. Intended for students in kindergarten through third grade"--
Includes bibliographical references and index.
Keywords: Manatees -- Juvenile literature; Manatees -- Conservation -- Juvenile literature